Representações culturais de gênero em fotografias da revista Illustração Paranaense (1927-1933) - Pinheiro, Ana Carolina Martins (2024)
This dissertation analyzes gender representations in the photographs published by Illustração Paranaense magazine between 1927 and 1930, investigating how these images contributed to the construction of an idealized “Paranist Citizen”, aligning ideals of femininity with the values of modernity and civilization. The research adopts key concepts such as gender, understood as a social construct that organizes sexual differences, and representation, which refers to the production of meanings through images that influence identities and discourses. The methodology combines feminist perspectives by Griselda Pollock and Joan Scott, the analytical method of Letícia Pedruzzi, and Ana Mauad’s semiotic analysis, allowing for the interpretation of images within their historical and cultural context. The analysis demonstrates that the magazine prioritized specific femininities, such as declaimers and muses, while marginalizing groups like poor, black, and immigrant women, who were represented symbolically or subordinated to economic development. The photographs functioned as tools for imposing social norms, reinforcing the gender expectations of the period. The dissertation concludes that revisiting these visual sources offers a deeper understanding of the media’s role in configuring social identities within the Paranist context, contributing to a broader analysis of gender representations in Paraná’s modernity.